Managing assessment in online and offline adult learning environments: a meta-review - Railean, Elena Aurel; Saltykova-Vaukovich, Maryna; Mkhabela, Zoleka (Edukacja Dorosłych, 2025)
In recent years, there has been exponential growth in the number of research studies on assessment, testing, measurement, and evaluation strategies in online and/or offline learning settings. The efficiency of the management of these methods and their presence in higher education has not, however, been confirmed by a meta-review. Management of assessment receives much attention at the frontier of education studies since it provides the opportunity to plan, monitor, and control learning processes and outcomes. However, not only do many educational managers find this approach demanding, but it also remains unclear what they should do to foster assessment, measurement, and evaluation management standards in nowadays learning processes, which are in online and/or offline learning environments. This study explores the specific features educational managers use to promote the management of assessment, measurement, and evaluation strategies in their professional activities. The article adopts the metasystem transition methodology. After searching for data related to global trends in empirical studies on assessment, evaluation, learning environment, and educational management, the priority of formative assessment was identified. Analyses revealed different perspectives on using formative assessment in educational management strategies. The results show that the metasystems perspective evidences the importance of research on the specifics of educational management in online and/or offline learning environments for the sustainability of higher education.